Moisey Mikhaylovich Pistrak: Russian Pedagogy, Education and Revolution (Research, Society and Development, 2020)
This article deals with Russian Pedagogy, its historical context and the contributions of this movement to the education of the time. Thus, the general objective is to analyze the contributions of Pistrak and his works in the movement called Russian Pedagogy. To this end, a theoretical study was carried out, a bibliographic study centered on the context of ancient Russia and the Pedagogy movement between 1917 and 1932. The focus was the author Moisey Mikhaylovich Pistrak and the school of work. Finally, it was observed that the school of work aimed at the formation of a new socialist society. In this sense, the nature of education, the cultural role of the school of work and the relationship between science and work are the three conclusions drawn by Pistrak on school work. Thus, a more concrete definition of the word work is to have a participation in the student's life and in its social construction, both inside and inside the classroom and science as a generalized and systematized guiding practice of this activity